Stability of non-centrosymmetric phases in tetra-coordinated of LDTM intercalates - Shkvarin, A; Postnikov, M.S.; Pryanichnikov, S.V.; Titov, A.N. (Eurasian Journal of Physics and Functional Materials, 2026)
On the basis of comparison of temperature dependences of lattice parameters of CuCrSe2 and Cu0.5ZrSe2 in the temperature region including transition between phases with centrosymmetric and noncentrosymmetric distribution of copper on positions tetrahedrally coordinated by selenium. It is concluded that the critical factor that ensures the stability of the non- centrosymmetric copper distribution is the covalent interaction between copper and selenium sublattices. This effect is not related to the anisotropy of the elastic constants of the lattice and can be observed in other layered structures with copper tetrahedrally coordinated by chalcogen.Recommended CitationShkvarin, A. S.; Postnikov, M.S.; Pryanichnikov, S. V.; and Titov, A. N. (2023) "Stability of non-centrosymmetric phases in tetra-coordinated of LDTM intercalates," Eurasian Journal of Physics and Functional Materials: Vol. 7: No. 4, Article 6.DOI: https://doi.org/10.32523/ejpfm.2023070406